2007
DOI: 10.1111/j.1745-7254.2007.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of PTEN involved in rosiglitazone-induced apoptosis in human hepatocellular carcinoma cells

Abstract: Aim: To investigate the effects of rosiglitazone, a peroxisome proliferator-activated receptor gamma (PPARγ) agonist, on the expression of the phosphatase and tensin homologue deleted on chromosome 10 gene (PTEN) and cell growth in hepatocellular carcinoma cells, as well as the underlying mechanisms of these effects. Methods: RT-PCR and Western blotting analyses were performed to detect transcription and the expression of PTEN in Hep3B cells treated with rosiglitazone. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 29 publications
4
29
0
Order By: Relevance
“…These data demonstrate that miR-371b-5p regulates PTEN expression post-transcriptionally by directly targeting its 3′UTR. We further used the PPARγ agonist Rosiglitazone, which can activate PTEN expression transcriptionally [38, 39], to treat hiPSC-ATIICs for 24 hours after transfection with miR-371b-5p mimic. As mRNA of PTEN can be significantly induced by Rosiglitazone in a dose-dependent manner (data not shown), Rosiglitazone is able to compete the miR-371b-5p mimic-mediated degradation of PTEN mRNA in hiPSC-ATIICs.…”
Section: Resultsmentioning
confidence: 99%
“…These data demonstrate that miR-371b-5p regulates PTEN expression post-transcriptionally by directly targeting its 3′UTR. We further used the PPARγ agonist Rosiglitazone, which can activate PTEN expression transcriptionally [38, 39], to treat hiPSC-ATIICs for 24 hours after transfection with miR-371b-5p mimic. As mRNA of PTEN can be significantly induced by Rosiglitazone in a dose-dependent manner (data not shown), Rosiglitazone is able to compete the miR-371b-5p mimic-mediated degradation of PTEN mRNA in hiPSC-ATIICs.…”
Section: Resultsmentioning
confidence: 99%
“…PPARγ is a nuclear receptor with multiple biologic effects. Recent evidence has demonstrated that PPARγ activation by TZDs inhibits cell growth and induces cell apoptosis in liver cancer cell lines [24,25] . Moreover, rosiglitazone, as a PPARγ synthetic ligand, has been shown to enhance the antitumor www.chinaphar.com Cao LQ et al Acta Pharmacologica Sinica npg activity of some chemotherapeautic drugs by the modulation of cancer cell agents [26,27] .…”
Section: Discussionmentioning
confidence: 99%
“…Most HCC cases occur in either Eastern Asia, especially in China, or sub-Saharan Africa [1] . Currently, the prognosis for HCC is still poor, as no effective therapy has been developed [2] . Gene targeting is a relatively new approach to cancer therapy, and a key requirement of gene targeting therapy is to have specific and efficient targets.…”
Section: Introductionmentioning
confidence: 99%